Solidarity - Nature, grounds, and value - Sangiovanni, Andrea (Manchester University Press, 2024)
In a world of deep political divisions and rising inequality, people feel the need for some form of collective resistance and transformative joint action. Calls for solidarity are heard everywhere. This book presents a critical proposal to guide our reflection on what solidarity is and why it matters. How is solidarity distinct from related ideas such as altruism, justice and fellow-feeling? What value does acting in solidarity with others have? In his lead essay, Andrea Sangiovanni offers compelling answers to these questions, arguing that solidarity is not just a fuzzy stand-in for feelings of togetherness but a distinctive social practice for an anxious age. His ideas are then put to the test in a series of responses from some of the world's foremost philosophers and political theorists.